Assessing Saudi learners’ engagement with social media in English classrooms - Jamshed, Mohammad; Alam, Iftikhar; Almashy, Abduh; Warda, Wahaj Unnisa (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study assessed Saudi English as a foreign language (EFL) learners’ perspectives on utilizing social media for educational and instructional activities, their experience with learning and teaching on social media, and how frequently they utilize these platforms to improve their language skills. The researcher randomly selected 288 EFL students from male and female campuses of College of Science and College of Business Administration, Prince Sattam bin Abdulaziz University. Respondents answered a questionnaire containing modified items from earlier studies. The data collected was examined using quantitative methods. The findings of the study revealed that tech-savvy Saudi EFL learners held exceptionally positive attitudes toward social media utilization as an effective language learning tool. It was also revealed that both learners and instructors had a very positive experiences utilizing social media for educational purposes, commonly employing it for different academic and educational activities in EFL classes. The study has implications for students and instructors because social networking sites and social media may be tailored to meet the demands of tech-savvy Saudi learners when conventional instruction no longer conforms to the taste of modern learners.